Reconstructing Standards for the Assessment of Electronic Evidence in Indonesian Civil Procedure from the Perspective of ISO/IEC 27037:2012 - Appe Hutauruk; Adalin Ali; Hotman Sinambela (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
Article 5 of Indonesia’s Electronic Information and Transactions Law recognizes electronic evidence as legally valid. However, civil procedure, which still relies on the Herzien Inlandsch Reglement/Rechtreglement voor de Buitengewesten (HIR/RBg), lacks procedural standards to ensure the integrity of electronic evidence. Unlike criminal proceedings supported by investigators and forensic laboratories, civil litigants independently collect, store, and submit electronic evidence, creating risks of manipulation and inconsistent judicial assessment. This study examines the normative gap concerning the chain of custody of electronic evidence and proposes ISO/IEC 27037:2012 as a framework for judicial evaluation. Employing normative juridical research with statutory, conceptual, comparative, and case approaches, the study analyzes Decision No. 258/Pdt.G/2023/PN Blb, supported by Constitutional Court Decision No. 20/PUU-XIV/2016 as its doctrinal foundation. The findings reveal that the court assessed WhatsApp screenshots using the doctrine applicable to documentary photocopies rather than Articles 5 and 6 of the ITE Law, admitting even photocopies of photocopies without examining the original electronic data. The absence of acquisition and preservation standards leaves the evidentiary value of electronic evidence dependent on judicial discretion, creating the potential for inconsistent decisions. To address this deficiency, the study proposes a three-pillar framework: imposing a bewijsvoering obligation on the submitting party, adopting the four stages and four principles of ISO/IEC 27037:2012 as judicial assessment criteria, and strengthening the role of accredited digital forensic experts. Consistent with Federal Rules of Evidence Rules 902(13)–902(14) and the doctrine of spoliation of evidence, this framework can be implemented through a Supreme Court Regulation, shifting judicial assessment from evaluating only electronic content to examining the integrity of evidence acquisition, preservation, and authentication.